2000
DOI: 10.3102/00028312037003633
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of the Antecedents of Emergent Spanish Literacy and Middle-School English Reading Achievement of Spanish-Speaking Students

Abstract: Among students entering kindergarten speaking Spanish, those with greater emergent Spanish literacy development and oral English proficiency were better able to maintain grade level performance in Spanish reading, transition more quickly to English reading, and attain a higher level of English reading proficiency in middle school. Non-English speaking student success in learning to read in English does not rest exclusively on primary language input and development, nor is it solely the result of rapid acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 21 publications
8
108
1
2
Order By: Relevance
“…Whereas previous research has uncovered many of the factors related to story comprehension in L1 children (e.g., Nagy et al, 1993;Reese et al, 2000), the third research question in our study focused on variables related to story comprehension in children learning English as a second language. Moreover, the current study also examined the role of metacognitive factors, including theory of mind, in L2 children's story comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas previous research has uncovered many of the factors related to story comprehension in L1 children (e.g., Nagy et al, 1993;Reese et al, 2000), the third research question in our study focused on variables related to story comprehension in children learning English as a second language. Moreover, the current study also examined the role of metacognitive factors, including theory of mind, in L2 children's story comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Although factors related to reading comprehension have been thoroughly explored in L1 children (e.g., Nagy, Garcia, Durgunoglu, & Hancin-Bhatt, 1993;Reese, Garnier, Gallimore, & Goldenberg, 2000), few researchers have examined variables related to story comprehension for children learning English as a second language (e.g., Hoover & Gough, 1990;Proctor, Carlo, August, & Snow, 2005). In addition, the relative contribution of meta-cognitive factors, including theory of mind, to story comprehension has largely been unexplored, particularly in L2 learners.…”
Section: Story Comprehensionmentioning
confidence: 99%
“…By providing an intervention that can be used in a bilingual setting, nonEnglish-speaking parents are given an important tool for participation in their child's early education which in turn gives the child better education outcomes. Studies suggest that early encounters with literacy in any language will foster later literacy development [34]. Efforts to improve school readiness are most effective when they address the capacity of families and communities to provide developmentally enhancing opportunities for their young children [35].…”
Section: Discussionmentioning
confidence: 99%
“…Reese et al (2000) found that many Latino parents believe that children under age 5 are not yet ready to understand the reading process and therefore do not engage in certain emergent literacy practices that are expected in schools. In our own work, we found that Latino parents were interested in, and capable of reading to their children; however, a variety of circumstances such as time, finances, and transportation limited their chances to do so.…”
Section: Shared Reading Practices Of Elsmentioning
confidence: 99%